The Influence Between Interpersonal Communication and Fear of Missing Out (FOMO) on Phubbing Behavior in Early Adults in Sidoarjo (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
The increasing use of the internet and smartphones, especially among early adults, has led to the phenomenon of phubbing. This study aims to analyze the effect of interpersonal communication and Fear of Missing Out (FoMO) on phubbing behavior. This study used a correlational quantitative approach, with a population of 574,827 early adults in Sidoarjo. this study involved 270 early adult samples selected through the Accidental Sampling technique. Data were collected using the interpersonal communication scale, fomo scale and phubbing behavior scale distributed via Google Form. The results of this study indicate a significant influence between interpersonal communication and fear of missing out on phubbing behavior in early adults. The amount of influence shows 26.1%, while the amount of partial influence on the interpersonal communication variable is 0.087%, while the fear of missing out variable shows 0.18%. This explains that fear of missing out contributes more to phubbing behavior.